Quadruple-Loop Learning: Success Analysis of the PAMAN TOPA Community Empowerment Program in Coral Reef Transplantation - Muhammad, Gandhi; Khoirulika, Rizka; Nurcahyo, Andik; D, Tristiayu Permata; Ardiansyah, Yanuar (International Journal of Social Service and Research, 2025)
The PAMAN TOPA (Pandanan Marine Techno Park) programme, a collaboration between PT PLN IP UBP Jeranjang, POKMASWAS Pandanan, and BPSPL Denpasar, successfully addressed coral reef transplantation failures caused by unsuitable media unable to withstand ocean waves and seawater corrosion. Using a quadruple-loop learning framework and descriptive qualitative methods, this study found that success stemmed from deep learning during problem-solving: learning from past failures, understanding problem characteristics, and considering relevant external factors. These insights shaped effective actions, including using FABA as a mixing agent for Block Macs media. Strong leadership, good coordination, and active participation further contributed to the outcome. The programme’s long, in-depth process offers valuable lessons and a replicable model for tackling similar challenges in the future.